Prescriptive explication of the normativity of meaning thesis - Kaluziński, Bartosz (Hybris, 2015)
The aim of this paper is to analyse prescriptive interpretations of the thesis that meaning is normative, which was introduced by Saul Kripke and later developed by Paul Boghossian. We are going to show that meaning prescriptivism is counter-intuitive and has implausible consequences. Attempts to save prescriptive interpretations by appealing to prima facie obligations or „normativity of judgment” are unsuccessful.